Economics / Thirteenth Edition - Nordhaus William D; Samuelson Paul A (Mcgraw Hill Book Company, 1989)
Preface, Basic Problems of Economic Organization, The Elements of Supply and Demand, Fundamental Concepts of Macroeconomics, Measurement of National Output and Income, Aggregate Supply and Business Cycles, Money and Commercial Banking, Macroeconomic Policy, Unemployment, Inflation and Unemployment, Microeconomics: Supply and Demand and Product Markets, Business Organization, Analysis of Costs, Imperfect Competition and Antitrust Policy, Wages and Rent and Profits: The Distribution of Income, Pricing of Factors of Production, Labor Unions and Collective Bargaining, Efficiency and Equity and Government, Markets and Economic Efficiency, Poverty and Equality and Efficiency, Economic Growth and International Trade, The Economics of Developing Countries, Protectionism and Free Trade, Epilogue, Glossary, Index.